A comparison of sources of baseline data for treatments of problem behavior following a functional analysis. Issue 1 (19th March 2019) - Scheithauer, Mindy; Schebell, Shannon M.; Mevers, Joanna Lomas; Martin, Clarissa P.; Noell, George; Suiter, Kerri C.; Call, Nathan A.
Abstract : It is common practice in research on the treatment of problem behavior to compare levels of targeted behaviors during treatment to levels when treatment is not in place. Some researchers use data collected as part of a multielement functional analysis as the initial baseline, whereas others collect new baseline data following completion of the functional analysis. We evaluated whether the source of baseline data influences the reliability and efficiency of decision‐making. Results suggest that similar decisions are made in regard to treatment efficacy using the different sources of baseline data, but using data from a multielement functional analysis as baseline may save time. Interrater agreement was adequate, but lower for some graphs than has been observed in past studies. Several potential explanations for this discrepancy are discussed.